1974
DOI: 10.1073/pnas.71.12.5109
|View full text |Cite
|
Sign up to set email alerts
|

The Organization and Diversity of Immunoglobulin Genes

Abstract: We have used purified mouse ih aunoglobulin light chain mRNA and synthetic DNA dich is complementary to it to assess the reiteration frequency of gene sequences corresponding to the K constant region of the mouse immunoglobulin light chain. These studies indicate that the constant region sequence is represented only two to three times per haploid mouse genome, a finding that rules out a simple stringent germ line mechanism which would require the constant region sequence to be represented hundreds if not thous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
2
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
0
20
2
1
Order By: Relevance
“…Their argument has been supported by the finding that there are few copies of light chain constant-region genes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and, more recently, by evidence derived directly from cloned immunoglobulin gene fragments (15,16). It has further been suggested that variable-and constant-region gene sequences are rearranged during the somatic differentiation of immunocytes so as to bring constant-and variable-region genes together (17,18).…”
mentioning
confidence: 54%
“…Their argument has been supported by the finding that there are few copies of light chain constant-region genes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and, more recently, by evidence derived directly from cloned immunoglobulin gene fragments (15,16). It has further been suggested that variable-and constant-region gene sequences are rearranged during the somatic differentiation of immunocytes so as to bring constant-and variable-region genes together (17,18).…”
mentioning
confidence: 54%
“…1º Tanto em camundongos (LEDER et al, 1974) quanto em plantas, cerca de 1% do genoma está comprometido com a elaboração de proteínas que protegem de forma específica seus hospedeiros contra patógenos: imunoglobulinas nos vertebrados, e PRs nas plantas.…”
Section: Resposta Integrada De Defesa Da Planta Contra a Infecção Do unclassified
“…From RNA-DNA hybridization studies, only a few copies of a particular C region seem to be present in the genome (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). The number of V region genes present in the germ line is still not resolved.…”
Section: Abstracimentioning
confidence: 99%